1998
DOI: 10.1093/brain/121.12.2221
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte progenitors are present in the normal adult human CNS and in the lesions of multiple sclerosis

Abstract: In multiple sclerosis, partial remyelination is conspicuous in many lesions, but widespread and lasting myelin repair ultimately fails as disability and handicap accumulate. Thus far, the precise identity of the cell responsible for limited spontaneous myelin repair has remained obscure. In the rodent, the proliferative oligodendrocyte progenitor is the most efficient remyelinating cell; this has now been identified in cultures prepared from normal human brain, but has proved difficult to demonstrate in situ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
189
2
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(202 citation statements)
references
References 43 publications
7
189
2
4
Order By: Relevance
“…Multi-potential precursors are abundant in many regions of the adult brain parenchyma [31][32][33][34]. In particular, oligodendrocyte progenitor cells (OPCs) were isolated from various regions of the adult rodent CNS [35][36][37], and were identified also in the adult human brain [38][39][40][41][42] and spinal cord [43]. OPCs are identified by expression of chondroitin-sulfate proteoglycan NG2+ and of platelet-derived growth factor receptor-α are highly abundant in the adult CNS, comprising up to 5% of its cells [37].…”
Section: Glial Progenitor Cells In the Adult Central Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-potential precursors are abundant in many regions of the adult brain parenchyma [31][32][33][34]. In particular, oligodendrocyte progenitor cells (OPCs) were isolated from various regions of the adult rodent CNS [35][36][37], and were identified also in the adult human brain [38][39][40][41][42] and spinal cord [43]. OPCs are identified by expression of chondroitin-sulfate proteoglycan NG2+ and of platelet-derived growth factor receptor-α are highly abundant in the adult CNS, comprising up to 5% of its cells [37].…”
Section: Glial Progenitor Cells In the Adult Central Nervous Systemmentioning
confidence: 99%
“…Some studies showed a depletion of progenitor cells after focal demyelination in experimental animals [52,74], whereas others showed that repeated episodes of demyelination did not slow down remyelination [75]. In pathological specimens of chronic MS lesions in human patients, neither decrease nor reactive increase was observed relative to normal white matter [39,[76][77][78]. This suggests that the response of the progenitor cell population to the demyelinating process in the human brain is deficient.…”
Section: Myelin Regeneration Fails In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…As with all regenerative processes the efficiency of remyelination decreases with age primarily due to a decrease in the ability of recruited cells to differentiate [32][33][34][35]. This age-associated decline in remyelination resembles and may be in part a determinant of a now well-recognized feature of many chronically demyelinated MS lesions, which are replete with oligodendrocyte lineage cells that are unable to differentiate into myelinating oligodendrocytes [36][37][38][39].…”
Section: Remyelination As Regenerative Therapymentioning
confidence: 99%
“…6 -12 Cells bearing specific surface markers [O4, galactocerebroside (GalC), chondroitin sulfate proteoglycan (NG2), proteolipid protein (PLP), platelet-derived growth factor receptor-␣ (PDGF-R␣)] or morphological features characteristic of myelin progenitor cells, are described in MS lesions. Phenotypic profiles of such cells include: O4 ϩ GalC Ϫ NG2 Ϫ , 13 PDGF-R␣ ϩ GalC Ϫ , 14,15 PDGF-R␣ ϩ , NG2 ϩ , 16 and PLP ϩ pre-OLGs. 17 These cells do not however appear to be overrepresented nor are they consistently proliferating in the lesions.…”
mentioning
confidence: 99%